Influence of competitive anxiety between different genders in racket sports - Woon, Yu Mei (2016)
The purpose of this research was to study how male and female racket players interpreted competitive anxiety. Previous studies have found gender differences in anxiety levels but few have delved into how both genders interpreted anxiety (Perry & William, 1998) which may have a more influential impact on game outcome than intensity alone (Pimienta, Weissbrod, Carter & Colangelo, 2014). The hypothesis was that men would interpret competitive anxiety as being more facilitative than women would. 32 badminton and squash players (16 males, 16 females) completed the Revised Competitive State Anxiety Inventory-2 (Cox, Martens & Russell, 2003) before their match and a post-competition questionnaire. A significant difference was found in the intensity of anxiety based on athletes’ gender, F(3, 28) = 3.07, p < .05; Wilks’ Ʌ = 0.75, partial ƞ2 = .25. Somatic anxiety negatively correlated to its direction for both males, r = - .82, p < .05, and females, r = - .68, p < .05. Self-confidence level had a significant positive correlation with its direction for both males, r = .74, p < .05, and females, r = .73, p < .05. Racket sports players of both genders could adopt coping techniques that lower somatic anxiety and raise self-confidence in order to perform better during competitions.